Changes in Aleut Concerns Following the Stakeholder-Driven Amchitka Independent Science Assessment - Burger, Joanna (Risk Anal, 2009)
There is widespread agreement that stakeholders should be included in the problem-formulation phase of addressing environment problems and, more recently, there have been attempts to include stakeholders in other phases of environmental research. However, there are few studies that evaluate the effects of including stakeholders in all phases of research aimed at solving environmental problems. Three underground nuclear blasts were detonated on Amchitka Island from 1965 to 1971. Considerable controversy developed when the Department of Energy (DOE) decided to “close” Amchitka. Concerns were voiced by subsistence Aleuts living in the region, resource trustees, and the State of Alaska, among others. This article evaluates perceptions of residents of three Aleutian village before (2003) and after (2005) the Consortium for Risk Evaluation with Stakeholder Participation’s (CRESP) Amchitka Independent Science Assessment (AISA). The CRESP AISA provided technical information on radionuclide levels in biota to inform questions of seafood safety and food chain health. CRESP used the questions asked at public meetings in the Aleut communities of Atka, Nikolski, and Unalaska to evaluate attitudes and perceptions before and after the AISA. Major concerns before the AISA were credibility/trust of CRESP and the DOE, and information about biological methodology of the study. Following the AISA, people were most concerned about health effects and risk reduction, and trust issues with CRESP declined while those for the DOE remained stable. People’s relative concerns about radionuclides declined, while their concerns about mercury (not addressed in the AISA) increased, and interest in ecological issues (population changes of local species) and the future (continued biomonitoring) increased from 2003 to 2005. These results suggest that questions posed at public meetings can be used to evaluate changes in attitudes and perceptions following environmental research, and the results are consistent with the hypothesis that the AISA answered questions about radionuclides, and lowered overall concern about radionuclides, but left unanswered concerns about the health effects of mercury.